Clinical dehydration and glomerular filtration rate in acute paediatric gastroenteritis. (7th June 2013) - Milani, Gregorio P; Fossali, Emilio F; Perri, Alessandra; Vettori, Arianna; Grillo, Paolo; Agostoni, Carlo
Abstract Aim To evaluate changes in glomerular filtration rate in acute gastroenteritis. Methods The correlation between two clinical diagnostic scales and glomerular filtration rate has been investigated in 113 children with acute gastroenteritis in a paediatric emergency setting. Results A significant reduction of GFR was found in 10% children less than, and 5% children higher than, 2 years of age with acute gastroenteritis. Conclusion The differences observed as for risk of renal hypoperfusion suggests to consider the age of children as an important determinant to consider the dehydration status in acute gastroenteritis.